2021
DOI: 10.3390/ijms222212275
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulin Based Self-Assembling Iron-Containing Protein Nanoparticles for Stem Cells MRI Visualization

Abstract: Over the past decade, cell therapy has found many applications in the treatment of different diseases. Some of the cells already used in clinical practice include stem cells and CAR-T cells. Compared with traditional drugs, living cells are much more complicated systems that must be strictly controlled to avoid undesirable migration, differentiation, or proliferation. One of the approaches used to prevent such side effects involves monitoring cell distribution in the human body by any noninvasive technique, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…We hope that the encapsulin-based label will allow us to study the growth and metastasis of 4T1-Qt tumors in vivo via MRI. Our previous study [ 13 ] has shown that the stable heterologous expression of Myxococcus xanthus encapsulin genes can be achieved in human mesenchymal stem cells (MSCs). The presence of transgenic sequences in cells did not reduce the rate of cell proliferation, and the T2 relaxation time of MSCs containing nanoparticles in encapsulins was significantly lower than the T2 relaxation time of intact MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hope that the encapsulin-based label will allow us to study the growth and metastasis of 4T1-Qt tumors in vivo via MRI. Our previous study [ 13 ] has shown that the stable heterologous expression of Myxococcus xanthus encapsulin genes can be achieved in human mesenchymal stem cells (MSCs). The presence of transgenic sequences in cells did not reduce the rate of cell proliferation, and the T2 relaxation time of MSCs containing nanoparticles in encapsulins was significantly lower than the T2 relaxation time of intact MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis was carried out as described earlier [ 13 ]. Briefly, 4T1-Qt cells were lysed using RIPA buffer, and the resulting lysate was precipitated (15 min, 14,000× g ).…”
Section: Methodsmentioning
confidence: 99%
“…Engineered encapsulins have shown potential as nanoreactors, , drug delivery systems, imaging agents, and immunotherapies. ,, Straightforward genetic and chemical shell modification allows small-molecule conjugation, peptide loop insertion, pore modification, ,, and fusion of protein domains to the N- and C-terminus of the encapsulin protomer. ,,, Recently, engineered encapsulins capable of triggered reversible disassembly, enabling in vitro cargo loading and stimulus-responsive cargo release, have also been reported …”
Section: Introductionmentioning
confidence: 99%
“…Engineered encapsulins have shown potential as nanoreactors, [50,51] drug delivery systems, [52] imaging agents, [5355] and immunotherapies. [30,56,57] Straightforward genetic and chemical shell modification allows small molecule conjugation, [33] peptide loop insertion, [58] pore modification, [50,59,60] and fusion of protein domains to the N- and C-terminus of the encapsulin protomer.…”
Section: Introductionmentioning
confidence: 99%
“…[46,47] This feature -a dedicated and modular protein loading mechanism -has been widely utilized to package non-native cargo proteins into the encapsulin shell via simple genetic fusion of TPs to proteins of interest. [48][49][50] Engineered encapsulins have shown potential as nanoreactors, [50,51] drug delivery systems, [52] imaging agents, [53][54][55] and immunotherapies. [30,56,57] Straightforward genetic and chemical shell modification allows small molecule conjugation, [33] peptide loop insertion, [58] pore modification, [50,59,60] and fusion of protein domains to the N-and C-terminus of the encapsulin protomer.…”
Section: Introductionmentioning
confidence: 99%